2015 21st International Conference on Automation and Computing (ICAC) 2015
DOI: 10.1109/iconac.2015.7313961
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of acoustic emissions for the frictional effect in engines using wavelets based multi-resolution analysis

Abstract: Abstract-The friction between piston ring-cylinder liner is a major cause of energy losses in internal combustion engines. However, no experimental method is available to measure and analyze the fictional behavior. This paper focuses on the investigation of using acoustic emission (AE) to characterize the friction online. To separate the effect relating to friction sources, wavelets multi-resolution analysis is used to suppress interfering AE events due to valve impacts and combustion progress. Then a wavelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The low frequency vibration response caused by the piston knock is likely to cover and suppress the response of the short-time asperity friction. Studies have shown that acoustic emission (AE) technology can effectively detect the dynamic response associated with friction events [26,27]. Acoustic emissions are the high frequency transient elastic waves that are spontaneously generated from a rapid release of strain energy caused by the deformation or fracture of materials.…”
Section: Experimental Verificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The low frequency vibration response caused by the piston knock is likely to cover and suppress the response of the short-time asperity friction. Studies have shown that acoustic emission (AE) technology can effectively detect the dynamic response associated with friction events [26,27]. Acoustic emissions are the high frequency transient elastic waves that are spontaneously generated from a rapid release of strain energy caused by the deformation or fracture of materials.…”
Section: Experimental Verificationmentioning
confidence: 99%
“…For piston rings and cylinder liner assemblies, these stress waves are induced by the asperity and viscosity friction effects. Both such effects are more proportional to relative velocity between the contacting materials [27]. Therefore, it is more convincing to use the AE signal after high-pass filtering to detect the friction event rather than the conventional vibration analysis.…”
Section: Experimental Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling studies try to describe the AE formation mechanism during the sliding friction based on different lubrication regimes. Based on well-known lubrication mechanisms, the sliding surfaces between the ring and liner generally have three lubrication regimes: boundary lubrication (BL), mixed lubrication (ML), and hydrodynamic lubrication (HL) [40]. It found that asperity contact was the AE source in sliding friction [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…To gain further insight into AE mechanisms for monitoring oil degradation, Nasha Wei et al [20] have applied discrete wavelet transform (DWT) to AE signals from the engine body to suppress noise influences and more accurately characterise the weak AE components relating to viscous friction. The authors also studied the potential impacts of alternative fuels on acoustic emission signals of the cylinder [21], which all show positive results.…”
Section: Introductionmentioning
confidence: 99%